Role of service quality in measuring customer satisfaction in power sector: a case of Dhaka Electric Supply Company (DESCO) - Jabber, Md. Wasim (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.